Sistem Penyeleksian Beasiswa Menggunakan Metode Simple Additive Weighting Pada Biro Akademik Kemahasiswaan dan Hubungan Masyarakat Universitas Negeri Jakarta - Andrew Alvaro Hazizi; Ria Arafiah; Mulyono (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2023)
Education is the key to improving quality of life, but the high cost of higher education often becomes a barrier. Universitas Negeri Jakarta (UNJ), through its Academic and Student Affairs Bureau and Public Relations (Bakhum), offers various scholarship programs. However, the selection and data management processes are still manual. This research designs and builds the Scholarship Selection Information System at Bakhum UNJ using the Simple Additive Weighting (SAW) method. This website-based system integrates criteria such as academic achievement, non-academic achievements, and financial conditions to determine scholarship recipients. The use of Laravel and MySQL ensures efficiency in data management. At the end of development, the system underwent black box testing to assess functionality and usability testing to evaluate its usefulness. The black box testing achieved 100% functionality, indicating that the system features operate as expected. Usability testing using Likert scale analysis yielded a usability score of 99.15%, indicating high suitability of the system. It is expected that this system will improve selection efficiency, save time, and ensure scholarships are awarded according to criteria. As a result, UNJ can support deserving students, enhance data management quality, and allocate scholarships more accurately.